Estimation of vitamins from selected edible weed - Ahmad Iqbal Muhamad (2015)
This research was conducted to estimate the amount of vitamins from eleven selected edible weeds. The sample weeds namely Piper Sarmentosum, Gynura procumbens, Stenochlaena palustris, Persicaria odorata, Piper betle, Paederia foetida, Passiflora foetida, Portulaca oleracea, Clinacanthus nutans, Amaranthus gangeticus and Plantago major were collected and analysed for vitamins content. The analyses were done in laboratories of Universiti Malaysia Kelantan, Jeli using UV/visible spectrophotometer to estimate the content of vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin C (ascorbic acid) and pro-vitamin A (carotenoids). Before analysis, the working samples were prepared in the laboratory as per the procedure mentioned in the laboratory manual. Each treatment was replicated four times and the data obtained were analysed statically following one way ANOVA using SPSS software. The mean values were compared by Post-Hoc's Duncan's test at P50.05°/0. Persicaria odorata has the highest content of vitamin B2 (2.194mg/100mg), whereas Amaranthus gangeticus has the highest vitamin B3 content of 1.740mg/100mg. The highest vitamin C (1 .557mg/100mg) content and highest pro-vitamin A (2.385mg/100mg) content were found in Stenochlaena palustris. These weeds can be tested further and consumed in our daily diet as cooked or as raw in salad.